2021
DOI: 10.1108/ijqss-07-2020-0108
|View full text |Cite
|
Sign up to set email alerts
|

Modeling spiritual intelligence on quality of work life of college teachers: a mediating role of psychological capital

Abstract: Purpose This paper aims to investigate the effect of spiritual intelligence on the quality of work life (QWL) of college teachers. Besides this, the mediating impact of psychological capital on improving their QWL and moderating effect of gender has also been examined in the study. Design/methodology/approach Variance-based structural equation modelling is used for testing the proposed structural model with a sample of 451 college teachers. Findings The findings of the study reveal that QWL is positively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
(74 reference statements)
2
9
1
2
Order By: Relevance
“…In order to quantitatively analyze the problems existing in college teachers, different indicators are used to analyze them [17,18]. e first-level indicators mainly include: professional ethics, professional quality, research tasks, research summary, and research environment [19,20]. e corresponding secondary indicators mainly include: ethics, professional attitude, faculty, theoretical basis, teaching ability, work pressure, physical and mental health, scientific research achievements, teacher evaluation, working environment, research pressure, and 1.…”
Section: Quality Monitoring and Evaluation Of College Teachersmentioning
confidence: 99%
“…In order to quantitatively analyze the problems existing in college teachers, different indicators are used to analyze them [17,18]. e first-level indicators mainly include: professional ethics, professional quality, research tasks, research summary, and research environment [19,20]. e corresponding secondary indicators mainly include: ethics, professional attitude, faculty, theoretical basis, teaching ability, work pressure, physical and mental health, scientific research achievements, teacher evaluation, working environment, research pressure, and 1.…”
Section: Quality Monitoring and Evaluation Of College Teachersmentioning
confidence: 99%
“…Past few literature notices remarkable gender gaps in several studies related to entrepreneurial intentions (Ruizalba Robledo et al. , 2015), OCB (Alexandra Beauregard, 2012) and spiritual intelligence (Singla et al. , 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Recent reports also showed that the more teachers rated themselves as self-compassionate, the greater their need for satisfaction and personal fulfillment (Moè and Katz, 2020), in addition, that when teachers are allowed to regulate their psychological emotions, these are related to a higher level of motivating teaching and therefore with their experience of satisfaction (Moè and Katz, 2021). Recent reports showed that the quality of working life is influenced by spiritual intelligence mediated by psychological capital (Singla et al, 2021). Another example given in a study involving 345 Pakistani teachers reported that communication is an influential factor in the quality of work life (Malik et al, 2019).…”
Section: Factors Affecting the Quality Of Life At Workmentioning
confidence: 99%